Effect of the modification of the cationic and anionic framework on the structural and electrical properties of lanthanum molybdates - López Vergara, Adrián; Bergillos-Ruíz, Marta; Porras-Vázquez, José Manuel; Marrero-López, David; Losilla, Enrique R. (My University, 2019)
Fluorinated lanthanum molybdates have been prepared at 1500 and 1200 ºC for 1 h and cooled down at 5 ºC min-1. The combination of anionic (F-) and cationic (Nb5+) doping stabilizes the cubic polymorph without needing a sudden cooling of the samples, increases the stability in reducing conditions and en-hances the electrical properties.
Keywords: Química inorgánica; Cristalografía; Mineralogía; Lanthanum molybdate; Fluorination; Polymorphism; Mixed ionic-electronic conductor; Proton conductivity; Cation and anion doping